An Entrepreneurship Venture for Training K-12 Teachers to Use Engineering as a Context for Learning - Anant R. Kukreti; Jack Broering (MDPI AG, 2019)
In this paper, the authors present their experiences from participating in a National Science Foundation (NSF) I-Corps L training program established for business startups, using Blank’s Lean LaunchPad, Osterwalder’s Business Model Canvas, and associated tools. They used the entrepreneurial skills acquired through this training to scale-up their emerging innovation, the Cincinnati Engineering Enhanced Math and Science Program (CEEMS), which had been developed, implemented, and evaluated with successful results over a period of seven years in a targeted 14 school-district partnership in Greater Cincinnati. The overriding goal was to improve student learning and success rates in K–12 math and science courses by helping to accelerate the process of bringing effective educational innovation, CEEMS, to scale. In CEEMS, teachers were trained in using challenge-based learning (CBL) and the engineering design process (EDP), teaching pedagogies to transform their classrooms into student-centered, hands-on learning environments, while also assisting students to improve their evaluation scores related to science, math, and engineering instruction. CEEMS teachers acquired the necessary skills through coursework, professional development (PD) workshops, and longitudinal professional guidance provided by assigned coaches over a period of two years to become proficient in developing CBL–EDP curriculum, teaching it, and assessing student learning and reflecting after teaching. The authors have documented how they used customer market research conducted during the I-Corps L training to define their minimum viable product (MVP) to duplicate the successful CEEMS methodology through a condensed (≤16 week) self-paced, completely online training program with virtual coaching support. The authors also describe the process they used to move forward very quickly from an MVP to a more complete product offering, its branding, the process of trademarking it, and finally licensing it to an established non-profit organization (NPO) for future marketing. Details of the whole experience are presented with the hope that it will serve as a useful guide for other venture creators.